2015
DOI: 10.1016/j.heares.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical representation of musical dyads: Individual differences and neural generators

Abstract: When two notes are played simultaneously they form a musical dyad. The sensation of pleasantness, or "consonance", of a dyad is likely driven by the harmonic relation of the frequency components of the combined spectrum of the two notes. Previous work has demonstrated a relation between individual preference for consonant over dissonant dyads, and the strength of neural temporal coding of the harmonicity of consonant relative to dissonant dyads as measured using the electrophysiological "frequency-following re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…Hence, models of consonance perception based on neural periodicity detection would be either incorrect, or at best incomplete, because they could not explain the perception of consonance at high frequencies observed in the current study. However, our results are not inconsistent with the notion that temporal coding may play an role in the perception of consonance in low frequency regions, and that inter-individual differences in temporal coding (Bones and Plack, 2015b), which can be partly due to factors such as musical experience (Bones et al, 2014) and aging (Bones and Plack, 2015a) may lead to changes in the perception of consonance. For example, it is possible to envisage a model in which the perception of consonance is based on a central harmonic template matching unit similar to the models proposed by Goldstein (1973) and Srulovicz and Goldstein (1983) for the perception of pitch.…”
Section: Discussioncontrasting
confidence: 74%
“…Hence, models of consonance perception based on neural periodicity detection would be either incorrect, or at best incomplete, because they could not explain the perception of consonance at high frequencies observed in the current study. However, our results are not inconsistent with the notion that temporal coding may play an role in the perception of consonance in low frequency regions, and that inter-individual differences in temporal coding (Bones and Plack, 2015b), which can be partly due to factors such as musical experience (Bones et al, 2014) and aging (Bones and Plack, 2015a) may lead to changes in the perception of consonance. For example, it is possible to envisage a model in which the perception of consonance is based on a central harmonic template matching unit similar to the models proposed by Goldstein (1973) and Srulovicz and Goldstein (1983) for the perception of pitch.…”
Section: Discussioncontrasting
confidence: 74%
“…Extrapolating from Bones et al’s (2014) model, we speculate that such effects might reflect the creation of additional noise in pitch processing due to interactions in the auditory periphery; however, there is no direct evidence at present to support this hypothesis. To address this, it might be fruitful to examine FFR responses to diotically versus dichotically presented BPCJ dyads, applying the electrophysiological methods of Bones and colleagues (2014, 2015) to assess whether the reduction in consonance ratings associated with the diotic presentation of relatively inharmonic dyads is mediated by diminished periodicity in the FFR signal. Beyond this, it might be worthwhile to replicate the present procedures using dyads with a higher average frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Bolstering their conceptual model, Bones and colleagues (2014) demonstrated that the relative harmonicity of the brainstem frequency following response (FFR) to conventionally consonant versus dissonant dyads was enhanced when chords were presented to both ears. This neural measure of the differential robustness of phase-locking to the frequency components of the chord spectrum predicted the relative consonance ratings of each dyad (Bones & Plack, 2015; Bidelman & Heinz, 2011). Although Bones et al (2014) only investigated responses to a very small number of conventionally tuned dyads and did not explicitly model their effects based on harmonicity differences between these dyads per se, their findings open the possibility that the association between harmonicity and consonance will generally be more pronounced when dyads are presented diotically versus dichotically.…”
mentioning
confidence: 99%
“…Anderson, et al, 2012,Tremblay, et al, 2004). In younger adults, poorer neural synchrony at the brainstem is predictive of poorer auditory processing and speech recognition (Bharadwaj, et al, 2015,Bones and Plack, 2015). Aging may exacerbate such deficits in neural synchrony as age-related morphologic and metabolic deficits in the auditory nerve, brainstem, and cortex, can result in atypical coding of temporal properties.…”
Section: Introductionmentioning
confidence: 99%